Pengaruh Senam GITA terhadap IMT dan HbA1C Pada Lansia dengan Diabetes Melitus - Anindini Winda Amalia; Paramita Ratna Gayatri; Hartati Tuna (Universitas Faletehan, 2020)
Physical exercise has become a therapeutic regiment in the management of diabetes mellitus. GITA gymnastics is a physical exercise that can be done by the elderly with diabetes mellitus to control their blood sugar levels. This research is quasi experimental with pre-post control group design. Respondents are elderly with diabetes mellitus in Prolanis, Kediri City. Respondents are 20 people, divided into two groups: gymnastic groups (10 people) and control groups (10 people). The gymnastic group was given GITA training for 12 weeks, 3 times a week, with duration of 30 minutes every session. Meanwhile, the control group wasn’t received treatment. The results of this study showed that the gymnastic group experienced a significant BMI change with p value 0.000001 (p <0.01) and the HbA1C of the gymnastics group experienced a significant change witn p value 0.000077 (p <0.05). In the T-test, there was a significant difference in the mean between BMI with p value 0.000006 (p<0.05) and HbA1C with p value 0.000006 (p<0.05) in the gymnastic group and the control group before and after the intervention. GITA exercise for 12 weeks is effective in controlling BMI and HbA1C in the elderly with diabetes mellitus.